A novel approach for generation of power by harvesting microwave from the ambient environment. Issue 1 (2nd January 2016) - Paulchamy, B.; Jaya, J.; Venkatesh, A.
ABSTRACT: To generate power by harvesting microwave from the ambient environment, this paper demonstrates the harvester operation and microwave signal strength analysis. The survey of signal was undertaken in urban and semi-urban regions, and the microwave signals available in space are digital television (DTV), GSM900, GSM1800 and 3G. Using the result of the survey, the harvester circuit was designed; the harvester circuit comprised mainly four parts, namely antenna, matching network, rectification and storage element. These four harvesters are generally known as rectenna. In order to capture the signal, at first, antenna was designed at printed circuit board (PCB) where the efficiency is low; therefore, the next method designed was patch-type antenna, which gives the efficiency greater than the PCB-type antenna. Finally, we got 3.3 V output voltage, which helps to charge the mobile phones without the need of wired process.